GOOGLE SLIDE DAN QUIZIZZ DALAM PENGEMBANGAN BUKU AJAR ELEKTRONIK INTERAKTIF (BAEI) MATEMATIKA - Arum Oktaliana Sari; Guntur Cahaya Kesuma; Dian Anggraini (AdMathEdu : Jurnal Ilmiah Pendidikan Matematika, Ilmu Matematika dan Matematika Terapan, 2019)
This study aims to determine the attractiveness and feasibility and effectiveness of learning implemented using interactive electronic textbooks (BAEI) assisted by Google slides and quizizz on the matrix material. This research method is research and development (R&D) with the Borg and Gall development model. There are 10 stages in this development namely 1) Potential and problems, 2) Data collection, 3) Product design, 4) Design validation, 5) Design revision, 6) Product trial, 7) Product revision, 8) Trial usage. 9) Product revision, 10) Mass production. Data collection instruments used were questionnaires given to material experts and media experts to determine product viability, and were given to students to find out the attractiveness of products that had been developed as well as pretest and posttest test instruments. The results of data analysis obtained from material experts and media experts stated that teaching materials developed were feasible to be used by obtaining "Valid" criteria with an average score of material experts of 3.76 and media experts of 3.48. Then the students' response to the electronic textbook (BAEI) in small group trials and large group trials (field) obtained the criteria of "Very Attractive" with the average score on the small group trial of 3.28 and the average results the score of large groups (field) is 3.49. The results of the effectiveness test analysis using effect sizes on the pretest and posttest obtained an average score of 0.72 and included in the medium category.